The near acoustic field of a circular aperture obtained by truncation of the semiinfinite cone vertex - Lysechko, V. O.; Kuryliak, D. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The characteristics of a near-field formation by the edge of a semiinfinite truncated cone under axial irradiation are established. Both soft and rigid surfaces are considered.